The Expression of miR-192 and Its Significance in Diabetic Nephropathy Patients with Different Urine Albumin Creatinine Ratio - Xiaoyu Ma; Canlu Lu; Chuan Lv; Can Wu; Qiuyue Wang (Journal of Diabetes Research)
Objective. To investigate the expression of miR-192 and its significance in diabetic nephropathy (DN) patients. Methods. 464 patients with type 2 diabetes mellitus (T2DM) were divided into normal albuminuria group (NA, n=157), microalbuminuria group (MA, n=159), and large amount of albuminuria group (LA, n=148). 127 healthy persons were selected as the control group (NC, n=127). The serum miR-192 levels were detected by Real-Time PCR and transforming growth factor-β1 (TGF-β1) and fibronectin (FN) were detected by enzyme-linked immunosorbent assay. The relationships among these parameters were analyzed by Pearson correlation analysis and multiple linear regression analysis. Results. The miR-192 in the LA group was significantly lower than other groups, which was lower in the MA group than in the NA group (P<0.01). The TGF-β1 and FN in the LA group were significantly higher than other groups, which were higher in the MA group than in the NA group (P<0.01). The expression of miR-192 was negatively correlated with TGF-β1, FN, and Ln (UACR) and miR-192, TGF-β1, and FN were independent relevant factors affecting Ln (UACR) in T2DM (P<0.01). Conclusions. These findings indicate that the levels of miR-192 were lower accompanied by the decrease of urine albumin creatinine ratio (UACR) and the association between miR-192 and nephritic fibrosis in DN.